Clove-Based Local Economic Development in Lede Sub-District, Taliabu Island District North Maluku Province - Pardin Isa; Endry Martius; Faidil Tanjung (Universitas Andalas, 2023)
This study aimed to identify and describe the clove agribusiness system and its economic prospects in supporting local economic development in Lede District, Taliabu Island Regency, North Maluku Province. The research was conducted using descriptive qualitative method. The results of this study suggest that Lede sub-district is one of the sub-district areas that is the base of clove agricultural development in Taliabu Island district. The developed clove commodity involves most of the farmers in the Lede Sub-district area, with a large development area, coupled with a high level of productivity. The clove commodity has potential economic value and has contributed to household income and the quality of clove farmers' welfare. To realize local economic development efforts based on the clove commodity, it is necessary to have the intervention of various parties, especially the local government and the private sector, both on the intervention in the scale of on farm and off farm activities, especially on a number of interventions related to infrastructure and superstructure supporting agricultural production activities, capital, to marketing management aspects and efforts to increase the economic added value of the clove commodity developed.